Transformative Islamic Law: Fazlurrahman's Study of Islamic Law Interpretation Towards Islamic Theoanthropocentrism - Hannani, Hannani; Haq, Islamul (LPPM IAIN Parepare, 2022)
Fazlurrahman's approach to reading the law differs from that of earlier interpreters; yet, his view of the law was essentially a concretization of the paradigm to which they subscribe. The purpose of this article was to examine Fazlurrahman's understanding on the transformation of Islamic law. Utilizing a literature review, the notion of Fazlurrahman's interpretation of Islamic theoanthropocentrism was thoroughly analyzed. According to the findings of the study, Fazlurrahman constructed a worldview that simultaneously centered on God and people. His hypothesis was dubbed the twofold movement theory by Rahman. Rahman has a holistic view of Islamic law. Islamic law was a continuity of faith, Islam, and ihsan doctrines.